A Cross‐Linked Flexible Metaferroelectrolyte Regulated by 2D/2D Perovskite Heterostructures for High‐Performance Compact Solid‐State Sodium Batteries - Yanan Huang; Zhuo Yang; Weicheng Zhou; Liequan Liu; Chuanbao Tu; Mingyang Tang; Haijiao Xie; Yu Lu; Xu Yan; Zhihao Ding; Xiaolong Li; Tiannan Yang; et al. (Advanced Science)
Abstract To address the issues of limited ionic conductivity and poor interface stability at room and low temperatures in solid‐state electrolytes, a robust intrinsic ferroelectrolyte or nanoferroelectrolyte strategy for engineering solid‐state flexible ferroelectric composite electrolytes utilizing strongly coupled intrinsic ion conducting 2D/2D sodium‐rich anti‐perovskite (NaRAP)/ferroelectric perovskite heterostructures is introduced. Herein, highly scalable PVDF‐based metaferroelectrolytes with Na2.99Ba0.005OCl/Ca2Na2Nb5O16− (CNNO−) nanosheets into a ferroelectric poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVDF‐HFP) matrix, through an in situ cross‐linking and spontaneous bridging method, for compact solid‐state sodium batteries (SSBs), are reported. Benefiting from unique well‐dispersed 3D ferroelectric coupled network and the Na2.99Ba0.005OCl/CNNO−‐induced PVDF‐HFP ferroelectric β phase, the Na+ flux is regulated, thereby inhibiting Na dendrite growth at the interface. Notably, the optimized PH‐5% NC metaferroelectrolyte exhibits rapid ion transport (1.11 × 10−4 S cm−1 at 25 °C), a wide electrochemical window (> 4.8V), superior conformal mechanical compatibility, improved flexibility, good elasticity and flame retardancy. The solid‐state Na3V2(PO4)3/PH‐5% NC/Na batteries present a stable cycling performance (remaining 56.4 mAh g−1 after 500 cycles at 1 C) even at 0 °C, potential for cost‐effective, safe, stable and compact SSB energy storage over 600 Wh L−1, vastly surpassing 365 Wh L−1 of the current commercial sodium‐ion liquid‐electrolyte batteries.